2010
DOI: 10.1258/shorts.2010.010077
|View full text |Cite
|
Sign up to set email alerts
|

Impact of visual art in patient waiting rooms: survey of patients attending a transplant clinic in Dumfries

Abstract: BackgroundThe clinic waiting area in Dumfries received the highest score among nine units offering transplant follow-up (p < 0.001 for differences between units) in the recent Quality Improvement Scotland Renal Transplant Survey.DesignThe purpose of the present study was to determine which aspects of the Dumfries waiting area patients considered important to their outpatient experience.MethodsWe posted a questionnaire to all 44 renal transplant patients attending the Dumfries Renal Unit in October 2009 in whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 5 publications
3
19
0
Order By: Relevance
“…The study highlights how the patient's sensory response is triggered or controlled by spatial elements, producing experience in viewing activities. Other studies affirm such argument, demonstrating how spatial elements can shape a patient's experience in space (Sonke et al, 2015;Belfiore, et al, 2015;Lankston, et al, 2010;Nanda et al, 2012;Cusack et al, 2010). Exploring openings that could be changed in size, the experiment requires children and adult respondents to put their hands through the openings.…”
Section: Seeing As a Transactionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study highlights how the patient's sensory response is triggered or controlled by spatial elements, producing experience in viewing activities. Other studies affirm such argument, demonstrating how spatial elements can shape a patient's experience in space (Sonke et al, 2015;Belfiore, et al, 2015;Lankston, et al, 2010;Nanda et al, 2012;Cusack et al, 2010). Exploring openings that could be changed in size, the experiment requires children and adult respondents to put their hands through the openings.…”
Section: Seeing As a Transactionmentioning
confidence: 99%
“…Architects and designers need to carefully choose the appropriate visual approaches that contribute positively and to greater effects on the wellbeing and health to their patient, and therefore improve the healing process of patients in the healthcare environment. (Valdez & Mehrabian, 1994;Ulrich, 1991;Cusack et al, 2010). Considering physical environment in a process design of facilities for patient is a vital role in architecture for healthcare.…”
Section: The Role Of Seeing In Healthcare Environmentmentioning
confidence: 99%
“…found that viewing a nature video positively affected physiological measures such as pulse rate when having blood drawn at a blood donor bank. With regard to content, research has repeatedly demonstrated the preference for representational scenes of nature (Cusack, Lankston, & Isles, 2010;Eisen, Ulrich, Shepley, Varni, & Sherman, 2008;Hathorn & Nanda, 2008;Ulrich & Gilpin, 2003).…”
Section: Positive Distractionmentioning
confidence: 99%
“…Studies such as the above-cited “EMA” studies and those like Gilpin et al ( 2006 ) suggested the need to consider the importance of outdoor and indoor features as determinant factors to smoking C-R. The effects of space features on affective processes and well-being has been studied especially in the context of healthcare environments (e.g., Cusack et al, 2010 ; Lankston et al, 2010 ). Urlich proposed a conceptual framework for evidence-based design of healthcare (Ulrich et al, 2008 , 2010 ) that included general and specific recommendations for built space features affecting mental state and behavior of patients and professional staff.…”
Section: Evidence-based Interior Design and Architecturementioning
confidence: 99%